Evaluation of Cyclic Instability for Steel at Low Cycle Straining - Lukša, Gražvydas; Stonkus, Mantas; Šniuolis, Raimondas (Jaunųjų mokslininkų darbai, 2017)
Having investigated 286 structural materials at low cycle straining the cycle properties of structural materials were evaluated by mechanical characteristics. The investigation showed that cyclically stable materials were in the same intervals as the cyclically unstable (hardened, softened) according to the ratio of the Rm / ReL ir (Rm / ReL)Z and similarly in the coordinates Rm / ReL – Z, therefore the grouping of structural materials according to the cyclic properties failed. In order to carry out a thorough analysis of the results, the cyclic stress-strain curves parameter α, which characterizes the intensity of cyclic hardening or softening of structural materials at room and elevated temperatures most precisely, was chosen.
Keywords: low cycle straining; cyclic hardening; softening and stabilization